FilmCraft. - Macnab, Geoffrey (Taylor and Francis, 2013)
Responsible for hiring all members of cast and crew from the director onwards, the producer's role is central to the making of any film and responsibilities can include everything from script development to securing financing to masterminding a film's marketing campaign. While few film producers are household names, they wield a degree of control that only the biggest name directors can aspire to. As with all of the FilmCraft titles, this book is based on new indepth interviews and features such greats as Tim Bevan, Marin Karmitz, Jeremy Thomas, Jon Kilik, Lauren Shuler Donner, Jan C.